Orientación sexual y su influencia en los embarazos de adolescentes de 15 a 19 años de la Unidad Educativa José María Estrada Coello del cantón Babahoyo. octubre 2018- abril 2019 - Aguirre López, Yulexi Vanessa (2019)
The present investigative work envisages an important explanatory text of how adolescents can prevent pregnancy and sexually transmitted diseases and therefore they have extensive knowledge about the meanings of terminologies and it will be a benefit for the José Maria Estrada Educational Unit Neck of the Babahoyo Canton of the Province of Los Ríos. In order to adduce this research project, a thorough bibliographic research on sexuality, sexual orientation and unwanted pregnancies was elaborated. To verify this project, 33 students between the ages of 15 and 19 years were screened, to which an observation was made in their school activities and a survey that will help confirm the hypothesis of this research work, the results of the instruments that were applied to the sample were analyzed and interpreted in order to subsequently draw conclusions and recommendations on the subject.